INFLOW AND OUTFLOW FACIES FROM THE 1993 TSUNAMI IN SOUTHWEST HOKKAIDO - Nanayama F.; Shigeno K. (My University, 2006)
We describe in detail the sedimentary facies, provenance and grain-size distributions of the 1993 tsunami deposits in the lower reaches of Usubetsu River. Only two lithofacies were recognized, a gravel lobe facies (GLF) and a sand-sheet facies (SSF). The gravel lobe facies was deposited rapidly by a hydraulic jump. In contrast, the sand-sheet facies, which contains both current ripples and dunes, was deposited by a traction current under subcritical flow conditions. We identified four stratigraphic units: Unit 1, Unit 2, Unit 3, and Unit 4, in ascending order. We interpreted Units 1 and 2 as having been deposited by the inflow and outflow events of the first run-up and Units 3 and 4 by the inflow and outflow events of the second run-up, respectively. Units 3 and 4 were more widely distributed and coarser grained than Units 1 and 2 because the second run-up was larger than the first run-up. Furthermore, Unit 4 was more widely distributed than Unit 3 because the outflow eroded the inflow deposits. Grain-size distributions of the inflow and outflow deposits were clearly different. Unit 4 deposits had a peak at 2.5 phi (P-1 population). In contrast, Unit 3 deposits had a bimodal distribution with peaks at - 0.5-1.5 phi (P-2 population) and at 2.5 phi (P-1 population). A comparison of the tsunami deposits with other sedimentary deposits near the study area showed that the tsunami deposits were mainly derived from the seabed at depths below 5.5 m in the offshore area, where the marine sands are about 2-2.5 phi in size and thus are the source of the P-1 population. The P-2 population is derived from coarse (0.5-2 phi) fluvial materials eroded during the tsunami run-up. According to our calculations, benthic foraminiferal tests were entrained from the comparatively deep seabed (at depths up to 100 m) during the tsunami run-up and included in the tsunami deposits. © 2006 Elsevier B.V. All rights reserved.
Keywords: 1993 HOKKAIDO-NANSEI-OKI TSUNAMI; BENTHIC FORAMINIFERAL TESTS; GRAIN SIZE; SEDIMENTARY FACIES; SEDIMENTARY PROCESSES; TSUNAMI DEPOSIT